Sonicated waves procedure effect on stabilizing expansive soil by nano-clay: Treat with cause - Sharo, Abdulla A.; Khasawneh, Mohammad A.; Bani Baker, Mousa; Al Tarawneh, Dana M. (Frontiers in Built Environment, 2022)
The use of hydrophilic bentonite nanoclay to improve the geotechnical properties of expansive soils was studied. Sonic waves and manual mixing for two expansive soils (taken from two different locations in Jordan) were studied; thereafter, a comparison between the results obtained from both methods was carried out. Different percentages of nanoclay were added to the two soils: 0, 0.1, 0.3, 0.5, 0.8, 1, 1.5, and 2.5% by dry weight of soil. Their impacts on compaction, unconfined compression strength (UCS), and free swell index (FSI) were investigated. For both methods of mixing, adding nanoclay to the soils resulted in a significant enhancement in strength and a reduction in swell properties of the soils. The UCS results of sonicated samples treated with 0.5% of nanoclay addition showed an increase of 27%–57% and a reduction in FSI by 41%–46.5%. Nevertheless, the UCS of non-sonicated samples treated with 1% of nanoclay showed an increase of 19.3–28.5% and a reduction in FSI by 37.3–44.3%.